Teachers' perceptions of teaching mathematics topics based on STEM educational philosophy: A sequential explanatory design - Ibrahim Khalil; Amirah AL Zahrani; Bakri Awaji; Mohammed Mohsen (STEM Education)
STEM education has gained significant attention in educational systems, and integrating mathematics into STEM education is a crucial issue in mathematics education. As teachers are considered highly influential in the educational process, we aimed to identify mathematics teachers' perceptions of teaching mathematics topics within the context of STEM education. We employed a mixed-methods sequential explanatory design. The quantitative sample included 248 mathematics teachers (99 males and 149 females) from the Bisha Governorate in Saudi Arabia. A questionnaire encompassing three dimensions (teachers' perceptions of teaching competence, teachers' perceptions of student interaction and motivation, and teachers' perceptions of the suitability of mathematics textbook content) was used to collect data, and its validity and reliability were verified. Qualitative data were gathered through interviews with eight participants. The results showed that mathematics teachers' perceptions of teaching mathematics topics based on the principles of STEM education were positive at the 'agree' level, with an overall mean of 2.41. The dimensions were ranked as follows: Teachers' perceptions of their STEM teaching competence (M = 2.49), perceptions of the suitability of mathematics textbook content for STEM-based practice (M = 2.47), and perceptions of their students' interaction and motivation when teaching mathematics in line with STEM (M = 2.26). There were no statistically significant differences in perceptions due to gender, teaching experience, or educational stage. The qualitative findings attributed the positive perceptions of teaching competence to factors such as the integration of technology and the inherent connections between mathematics and other subjects. However, designing STEM-integrated tasks was challenging due to lack of STEM training and knowledge. Limitations in student interaction were linked to students' limited understanding of STEM, teachers' beliefs, and students' weak mathematics skills. The participants viewed textbook content positively, citing STEM-related components.